Myocardial Function Maturation in Very-Low-Birth-Weight Infants and Development of Bronchopulmonary Dysplasia - Méndez-Abad, Paula; Zafra-Rodríguez, Pamela; Lubián-López, Simón; Benavente-Fernández, Isabel (Frontiers in Pediatrics, 2020)
Background: Myocardial function in very-low-birth-weight infants (VLBWIs) develops during early postnatal life, but different patterns of temporal evolution that might be related to the development of bronchopulmonary dysplasia (BPD) are not completely understood. Methods: A prospective cohort study including VLBWIs admitted to our NICU from January 2015 to January 2017 was conducted. Plasma N-terminal pro B type natriuretic peptide (NTproBNP) levels were measured, and echocardiograms were performed at 24 and 72 hours of life and weekly thereafter until 36 weeks of postmenstrual age (PMA). We measured the tricuspid annular plane systolic excursion (TAPSE) by M-mode; the lateral tricuspid E’, A' and S' waves; and the myocardial performance index (MPI) by tissue doppler imaging (TDI). The subjects were divided into non-BPD and BPD groups. Results: We included 101 VLBWIs. The TAPSE and E´, A´ and S´ waves increased while MPI-TDI decreased over time. Birth gestational age (GA) and postnatal PMA impacted these parameters, which evolved differently in those who developed BPD compared to those in the non-BPD group. The NTproBNP levels at 14 days of life and different echocardiographic parameters were associated with the development of BPD in different multivariate models. Conclusion: TAPSE and TDI values depend on GA and PMA and follow a different temporal evolution that is related to the later development of BPD. Combined biochemical and echocardiographic biomarkers can help identify which VLBWIs are at higher risk of developing BDP.